Barriers to the Use of Entomopathogenic Nematodes as Biocontrol Agents: South Africa as a Case Study: Barriers in using nematode biocontrol agents - Dunn, Murray D.; Malan, Antoinette P. (South African Journal of Enology and Viticulture, 2025)
Pesticides are synonymous with conventional agriculture, however in recent years, synthetic pesticides have been scrutinised for environmental and human health-related toxicity. Biopesticides are a sustainable alternative, with biopesticide technology promising to meet the market halfway by means of maintaining the current agricultural economic structure, using input technologies, but sustainably, to promote biodiversity and healthy ecosystem functioning. Biopesticides, which have the potential to mitigate the impact of ecosystem collapse from intense agriculture and climate change, have received heavy investment for product development. However, multiple barriers to biopesticide commercialisation are preventing their widespread use in viticulture and other South African agricultural industries. A literature review has established that the barriers can be simplified into three main categories: regulatory, commercial, and educational. This review seeks to understand the barriers and why, after many years of research and development and considerable investment, the South African biopesticide market is still only a fraction of the size of the synthetic product market. Global research is considered, as the issue is not a solely South African one, and multiple countries are facing similar barriers to achieving biopesticide commercial success. Moreover, this review provides the context as to why, after almost 20 years of research and product development, a locally produced entomopathogenic nematode biopesticide product is still unavailable to South African growers, despite the high demand for such a product.